SureCall: Towards Glitch-Free Real-Time Audio/Video Conferencing - Mondal, Amit; Cutler, Ross; Huang, Cheng; Li, Jin; Kuzmanovic, Aleksandar (2010 IEEE 18th International Workshop on Quality of Service (IWQoS), 2010)
Global enterprises are increasingly adopting uni- fied communication solutions over traditional telephone systems. Such solutions provide integrated audio/video conferencing and messaging services, and enable flexible working environments by allowing mobile and dispersed users to communicate and collaborate easily and efficiently. The ultimate goal of unified communications is to ensure a smooth and best possible user experience across all scenarios. To address this challenge and understand the impact of various network scenarios on unified audio/video conferencing, we have developed a distributed experimental platform – SureCall – and deployed it on over 80 machines across a global enterprise and many residential networks. SureCall has collected worth of more than 6 months of packet-level audio/video conferencing traces. Through in-depth analysis of these traces, we have quantitatively compared how key performance metrics, such as packet loss and jitter, as well as the correlation between them, are affected by the enterprise and residential networks, by WiFi connections and VPN links, etc. In addition, we show how SureCall can serve as an ideal platform to design, experiment and validate new schemes and algorithms. We have developed a new audio quality classifier using the SureCall platform, which is being experimented with the recent release of Office Communicator solution for large-scale validation.